2017
DOI: 10.1016/j.jstrokecerebrovasdis.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Balance Confidence Is Related to Features of Balance and Gait in Individuals with Chronic Stroke

Abstract: Reduced balance confidence is associated with impairments in features of balance and gait in individuals with sub-acute stroke. However, an understanding of these relationships in individuals at the chronic stage of stroke recovery is lacking. This study aimed to quantify relationships between balance confidence and specific features of balance and gait in individuals with chronic stroke. Participants completed a balance confidence questionnaire and clinical balance assessment (quiet standing, walking, and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
1
26
0
1
Order By: Relevance
“…The higher stride duration variability observed in less active individuals could be due to poorer self-efficacy for balance. 9,15,16 Individuals with poor balance confidence tend to focus more on their travel path while walking and less on potential obstacles in their path, 25 limiting their ability to anticipate necessary path adjustments to avoid pedestrians or obstacles. Therefore, gait variability may have been increased by the need to make more sudden, larger amplitude adjustments in stepping.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The higher stride duration variability observed in less active individuals could be due to poorer self-efficacy for balance. 9,15,16 Individuals with poor balance confidence tend to focus more on their travel path while walking and less on potential obstacles in their path, 25 limiting their ability to anticipate necessary path adjustments to avoid pedestrians or obstacles. Therefore, gait variability may have been increased by the need to make more sudden, larger amplitude adjustments in stepping.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, including measures of both walking ability and balance confidence in a predictive model still does not fully explain variance in ambulatory activity. 9 Gait variability, a measure of walking ability with a known association with fall risk and balance confidence, [14][15][16] may be a strong single predictor of ambulatory activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurological affected humans with reduced sensory information from the lower limbs and poor muscle strength to control leg movements also show wider step width [17]. Many studies have suggested that medial-lateral stability is very important for people to maintain balance and avoid falling [18]. The step width variability represents the more sensitive descriptor of locomotion control of older and young adults.…”
Section: Introductionmentioning
confidence: 99%